2021
DOI: 10.3892/mmr.2021.12041
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril/valsartan inhibits ox‑LDL‑induced MALAT1 expression, inflammation and apoptosis by suppressing the TLR4/NF‑κB signaling pathway in HUVECs

Abstract: The therapeutic effect of sacubitril/valsartan (S/V) on heart failure has been confirmed, while its role in atherosclerosis remains largely unexplored. The present study aimed to investigate the effects of S/V on the expression of metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), inflammation and apoptosis in human umbilical vein endothelial cells (HUVECs) induced by oxidized low-density lipoprotein (ox-LDL) and to elucidate its possible mechanism. Cell Counting Kit-8 assay was used to detect ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…According to previous studies, lipid profile, cTnI, infarct size, inflammation, and adhesion molecules are viewed as hallmarks of AMI 22 , 23 , 24 ; thus, we explored the association of lnc‐MALAT1 with them among AMI patients, which showed that lnc‐MALAT1 was positively linked with lipid dysregulation (reflected by LDL‐C), the marker of myocardial injury (reflected by cTnI), disease severity indicator (reflected by infarct size), systematic inflammation (reflected by CRP, TNF‐α, IL‐6, and IL‐17A), and adhesion cytokines (reflected by VCAM‐1 and ICAM‐1). The potential explanations might be that (1) lnc‐MALAT1 could accelerate lipid metabolism and lipid oxidation in AMI, which resulted in elevated LDL‐C 25 ; (2) lnc‐MALAT1 might promote cardiomyocyte injury through several mechanisms, such as regulating autophagy‐related 3, as well as phosphatase and tensin homolog deleted on chromosome 10, which led to increased cTnI and infarct size in AMI 26 , 27 ; (3) lnc‐MALAT1 might be able to accelerate inflammation by regulating several signaling pathways, including Wnt/β‐catenin and nuclear factor‐kappa B signaling; thereby, lnc‐MALAT1 was positively associated with inflammation in AMI patients 28 , 29 ; and (4) lnc‐MALAT1 could accelerate the production of adhesion molecules through several methods, such as microRNA‐590 and the signal transducer and activator of transcription 3 pathway 21 ; thus, a positive relation was found in lnc‐MALAT1 with adhesion cytokines among AMI patients. In addition, we also discovered that higher lnc‐MALAT1 was linked with a history of DM among AMI patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, lipid profile, cTnI, infarct size, inflammation, and adhesion molecules are viewed as hallmarks of AMI 22 , 23 , 24 ; thus, we explored the association of lnc‐MALAT1 with them among AMI patients, which showed that lnc‐MALAT1 was positively linked with lipid dysregulation (reflected by LDL‐C), the marker of myocardial injury (reflected by cTnI), disease severity indicator (reflected by infarct size), systematic inflammation (reflected by CRP, TNF‐α, IL‐6, and IL‐17A), and adhesion cytokines (reflected by VCAM‐1 and ICAM‐1). The potential explanations might be that (1) lnc‐MALAT1 could accelerate lipid metabolism and lipid oxidation in AMI, which resulted in elevated LDL‐C 25 ; (2) lnc‐MALAT1 might promote cardiomyocyte injury through several mechanisms, such as regulating autophagy‐related 3, as well as phosphatase and tensin homolog deleted on chromosome 10, which led to increased cTnI and infarct size in AMI 26 , 27 ; (3) lnc‐MALAT1 might be able to accelerate inflammation by regulating several signaling pathways, including Wnt/β‐catenin and nuclear factor‐kappa B signaling; thereby, lnc‐MALAT1 was positively associated with inflammation in AMI patients 28 , 29 ; and (4) lnc‐MALAT1 could accelerate the production of adhesion molecules through several methods, such as microRNA‐590 and the signal transducer and activator of transcription 3 pathway 21 ; thus, a positive relation was found in lnc‐MALAT1 with adhesion cytokines among AMI patients. In addition, we also discovered that higher lnc‐MALAT1 was linked with a history of DM among AMI patients.…”
Section: Discussionmentioning
confidence: 99%
“…lnc-MALAT1 could accelerate lipid metabolism and lipid oxidation in AMI, which resulted in elevated LDL-C 25 ; (2) lnc-MALAT1 might promote cardiomyocyte injury through several mechanisms, such as regulating autophagy-related 3, as well as phosphatase and tensin homolog deleted on chromosome 10, which led to increased cTnI and infarct size in AMI26,27 ; (3) lnc-MALAT1 might be able to accelerate inflammation by regulating several signaling pathways, including Wnt/β-catenin and nuclear factor-kappa B signaling; thereby, lnc-MALAT1 was positively associated with inflammation in AMI patients28,29 ; and (4) lnc-MALAT1 could accelerate the production of adhesion molecules through several methods, such as microR-NA-590 and the signal transducer and activator of transcription 3 pathway21 ; thus, a positive relation was found in lnc-MALAT1 with adhesion cytokines among AMI patients.…”
mentioning
confidence: 99%
“…As for the impacts of valsartan and tripterygium glycosides on TLR4 expression, a related study has reported that valsartan prevents glycerol-stimulated acute kidney injury via reducing the TLR4 and NF-kappaB expression [ 24 ]. Furthermore, in heart failure, it has been evidenced that valsartan can mitigate the inflammatory response by reducing TLR4 expression [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sacubitril/valsartan inhibits oxidized low-density lipoprotein-induced apoptosis in human umbilical vein endothelial cells and ameliorates endothelial injury by inhibiting the TLR4/NF-κB signaling pathway and downregulating metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) expression ( 24 ). Administration of sacubitril/valsartan to rats fed a high-protein diet with CRS downregulates mitofusin 2 (Mfn2) expression, inhibits mitochondrial division, protects the functional integrity of mitochondria, inhibits apoptosis, and improves cardiac function ( 25 ).…”
Section: Mechanisms Of Action Of Sacubitril Valsartan: Experimental E...mentioning
confidence: 99%